Optimal control of race car with aerodynamic slipstreaming effect - Liu, Xuze; Fotouhi, Abbas; Cecotti, Marco; Auger, Daniel (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This article presents a new method to describe the aerodynamics slipstreaming effect on the downstream car. This new approach can be implemented in lap time simulations (LTSs) and used to study the optimal trajectory of a downstream car operating in the wake of an upstream car. Two different scenarios are investigated using this method. In the energy-saving scenario for electric racing cars, the result shows the optimal strategy varies depending on the upstream car’s pace and the initial gap between the two cars. Chasing to stay in the wake is less effective when the initial gap is relatively big. In the overtaking scenario on an oval track, it is shown that the wake of the upstream car benefits the downstream car’s acceleration but, meanwhile, reduces the lateral performance limit of the downstream car due to downforce loss. In order to maintain a competitive performance, it is essential for the downstream car to choose an alternative racing line to drive outside the wake when braking and passing through a corner.
Keywords: Aerodynamic slipstreaming; lap time simulation (LTS); optimal control